Role of Academic Integrity in the Relationship between Imposter Phenomenon and Mental Health among University Students - Khalil, Saira; Aqil, Farah; Jadoon, Noor us Saba (Annals of Human and Social Sciences, 2024)
This study examines the relationship between the Imposter Phenomenon (IP), academic integrity, and mental health among university students, focusing on the potential mediating role of academic integrity. Using a sample of 441 students from Islamabad and Rawalpindi, the research employed the Clance Imposter Phenomenon Scale (CIPS), Academic Integrity Scale (AIS), and General Health Questionnaire (GHQ-12). Results showed that IP is significantly linked to poorer mental health, supporting the hypothesis that higher imposter tendencies lead to increased psychological distress. However, academic integrity neither predicted mental health nor mediated the relationship between IP and mental health. The study emphasizes the need for further research to explore other factors that may affect these relationships and develop interventions to support students experiencing IP and improve mental health outcomes.